Perancangan Aplikasi E-CRM Pada PT Manfuku Sejahtera Indonesia - Inayatulloh, Inayatulloh; Sukandi, Andi (ComTech: Computer, Mathematics and Engineering Applications, 2010)
The purpose of this research is to build an electronic Customer Relationship Management applications based computer by using Internet technology to enhance customer relationships. The research method is to do with company business process analysis in maintaining relationships with customers and develop computer-based applications that support enterprise business processes. In analyzing the company's business processes carried out several activities with the company to get the information required and the design of applications that will be built in accordance with needs. The conclusion the implementation of an electronic application web-based Customer Relationship Management can help companies improve relationships with customers based on questionnaires conducted several post-application. Conclusion of this paper is in improving relationships with customers built an electronic Customer Relationship Management applications based computer by using Internet technology that allows companies in gaining new customers, maintain customer loyalty with an intermediary application.